A Feasibiltiy study on ScanDry 6000 - Castillo, Corallie S.; Joson, Carlo Marx O.; Oberio, Erika R.; Rodriguez, Cherrylyne S. (Diliman, Quezon City College of Engineering, 2000)
ScanDry 6000 is the new equipment developed by SCANCON INC. It is a recirculating batch dryer which caters to different agricultural products such as rice, corn, cacao, coffee and peanuts that need to be dried. ScanDry 6000 is an economical alternative to the dominating current industry practice of sun drying. The Market study reveals that ScanDry 6000?s target market comprise of the cooperatives and millers of Regions 2 and 3, and the National Food Authority (NFA). Regions 2 and 3 are chosen because the volume of production of cereals (i.e. palay and corn) and the number of cooperatives established in those areas are relatively higher, as compared with other regions in the country. Moreover, the number of millers situated in the area is substantial enough. These are the result of the Target Market Selection. The demand trend was determined through the number of cooperatives and their production capacities (in terms of metric tons of palay and corn), part of production dried by the millers as well as the NFA. The demand in mechanical dryer units is as follows 171,640 from cooperatives, 74,194 from millers, and 41,221 for NFA. These historical demands are used to forecast the demand trend for the next five years (2001-2005). After evaluating several forecasting techniques, the linear regressions was selected. The forecasted demand graph show that there is an increasing demand for the next five years. The forecasted demand are: 103,756 for 2001, 105,214 for 2002, 106,672 for 2003, 108,131 for 2004 and 109, 589 for 2005. Industry Analysis shows that the current supply of mechanical dryers from Bureau of Postharvest Research Extension (BPRE) manufacturers and imported supplies (obtained from Department of Trade and Industry) is so scarce that there is a large gap between the demand and supply. The forecasted supply, determined through linear programming, shows a decreasing trend. This can be attributed to the fact that the product is durable in nature and there is a possible market saturation. The demand for the product was determined to be too great that the limiting variable for the market share to capture is the company?s projected capacity. Moreover, the percent willingness of the three market sectors were also determined through surveys and phase interviews and considered in the computation for the effective demand. It was found that the percentage amounts to less than 1% of the total demand. The sales plan of the company is to produce eighty (80) on the first year, eighty-eight (88) on the second, ninety-seven (97) on the third, one-hundred seven (107) on the fourth and one-hundred eighteen (118) on the fifth year. The marketing strategies evaluated are the 4P's namely: product, placement, pricing and promotions.
Feasibility study
Typescript
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: SCANCON INC; Food--Drying--Equipment and supplies; Drying equipment industry; Participatory monitoring and evaluation (Project management)